Dynamic Partial Reconfiguration with FIR Filter Application - Noopur Astik (International Journal of Reconfigurable and Embedded Systems (IJRES), 2015)
Dynamic partial reconfiguration has evolved as a very prominent state of art for efficient area utilization of Field Programmable Gate Array (FPGA) as well as significant reduction in its overall power consumption when properly used to lessen the idle logic on FPGA. It provides desired results even as the computational complexity increases in the field of Digital Signal Processing. This paper explains Dynamic Partial Reconfiguration (DPR) with an example of Finite Impulse response (FIR) filter of order 10. Initially RTL coding for Direct Form FIR structure is written in Verilog in fixed point format for low pass and high pass filter modules using ISE Design suite. Functioning of the both the modules is verified individually through hardware co-simulation on ZYBO (Zynq Board) from Digilent using Black Box from System Generator. Finally dynamic partial reconfigurable FIR filter with low pass and high pass as reconfigurable modules is implemented on ZYBO using PlanAhead tool. Final comparison of resource utilization with and without DPR is presented